KOMPARASI PENDAPATAN USAHATANI CABAI MERAH DAN PADI SAWAH DI LAHAN IRIGASI PADA MT I DI DESA TRIYOSO BELITANG OKU TIMUR - Muridin (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research is to: (1) Analyze how the history of red chili farming development on irrigated rice field at MT I in Triyoso Village Belitang Sub-District, OKU Timur Regency, (2) Analyze how the income difference between rice farming and red chili farming at MT I In Triyoso Village, Belitang District, OKU Timur Regency. This research was conducted in Triyoso Village, Belitang District, OKU Timur Regency. Site selection was done purposively with the consideration that Triyoso Village is the majority of village inhabitant as farmer and there are some farmers who have cultivated rice paddy and red pepper at MT I. The research will be conducted in June 2015. This research found That the cultivation of red chili has long been dilakanakan in Triyoso Village, but farmers who first cultivate red pepper continuously in irrigated rice fields is Mr. Mardiyanto in 2012. The average total production cost of red chili farming on MT I is Rp 12,487 .873 / Lg / MT, revenue of Rp 24,470,000 / Lg / MT, resulting in revenue of Rp 11,982,127 / Lg / MT. The average cost of paddy production production at MT I is Rp 11,568,939 / Lg / MT, the revenue is Rp 19,106,204 / Lg / MT, so the income is Rp 7.537.265 / Lg / MT. The value of R / C ratio of red chili farmers is 1.96, while the R / C ratio for rice farmers is 1.65 and there is a statistically significant difference between the income of red chili farmers and rice farmers. This can be seen from the value of t arithmetic of 18.36 and t table value is 2.10.